STRATEGI PENGEMBANGAN PRODUKSI JAGUNG PETANI LAHAN KERING PADA DAERAH PERBATASAN INDONESIA (STUDI KASUS DI DESA KOTABIRU KECAMATAM MOBALIMA TIMUR) - Delsi, Oliva; Un, Paulus; Illu , Abraham Ruylthon (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
This research aims to determine the development strategies for dryland corn farming by farmers in the border area of Kobalima Timur District, Malaka Regency. The determination of the location in this study was done intentionally with a sample size of 50 people. Data collection used interview, documentation, and observation techniques. The data used are primary data and secondary data. The method used in this research is the descriptive method, with SWOT analysis as the analytical tool. The research results show that the strategy for developing corn farming in Kotabiru Village focuses on the S-O strategy, which involves utilizing farmers' experience, generational farming skills, profitable corn prices, and the availability of potentially vast land to meet the continuously increasing demand for corn, the broad market demand, and the development of processed corn products.